Competition Analysis of Superior Product Heart Services a Medical Tourism Organizer in Medan - Destanul Aulia; Sri Fajar Ayu; Meutia Nauly (RIRAI Publisher, 2023)
This becomes increasingly important when this number increases every year with the development of information technology and aviation systems that are easier and cheaper. Only Covid has succeeded in reducing the number of medical tourists from North Sumatra to Penang. Since the beginning of 2022, North Sumatra has declared to be one of the world's medical tourism destinations. This is important not only to bring in foreign tourists, but at the same time to hide out the outflow of the North Sumatra community itself. There are seven hospitals that are launched will become medical tourism destinations in North Sumatra, one of which is a hospital that is studied for providing heart services which is the most sought, after service by the people of North Sumatra. Based on this phenomenon it is felt to be very important to conduct competition analysis of integrated heart service products organized by this hospital, so that the product you want to launch receives an appropriate welcome. The method used in this study is to use a descriptive strategy method related to supply side, demand side, and product competition obtained with structured questionnaires. The results of the study show that the service, the administrative process of type A hospitals in Medan is quite good but still must be evaluated and improved, while cleanliness and health protocols and facilities at type A hospitals in Medan are still below the